1999
DOI: 10.1017/s0029665199000609
|View full text |Cite
|
Sign up to set email alerts
|

Optimal nutrition: vitamin E

Abstract: Interest in the role of vitamin E in disease prevention has encouraged the search for reliable indices of vitamin E status. Most studies in human subjects make use of static markers, usually a-tocopherol concentrations in plasma or serum. Plasma or serum α-tocopherol concentrations of < 11.6, 11.6–16.2, and > 16.2 mmol/l are normally regarded as indicating deficient, low and acceptable vitamin E status respectively, although more recently it has been suggested that the optimal plasma α-tocopherol concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 74 publications
0
45
1
1
Order By: Relevance
“…Recently, it has been proposed that the adequate plasma concentration of α -tocopherol to prevent neoplasm and cardiovascular disorders is more than 30 μmol/l. 31 In contrast to Hozyasz et al, 32 who reported that in untreated patients the levels of plasma tocopherol were significantly lower compared with those on GFD, 32 we showed a significantly decreased serum concentrations of vitamin E in both celiac groups regardless of compliance with diet. Noteworthy, the GFD did not increase the level of this vitamin.…”
Section: Results Blood Tests In Controls and Celiac Patientscontrasting
confidence: 92%
“…Recently, it has been proposed that the adequate plasma concentration of α -tocopherol to prevent neoplasm and cardiovascular disorders is more than 30 μmol/l. 31 In contrast to Hozyasz et al, 32 who reported that in untreated patients the levels of plasma tocopherol were significantly lower compared with those on GFD, 32 we showed a significantly decreased serum concentrations of vitamin E in both celiac groups regardless of compliance with diet. Noteworthy, the GFD did not increase the level of this vitamin.…”
Section: Results Blood Tests In Controls and Celiac Patientscontrasting
confidence: 92%
“…Para alfa-tocoferol no soro: < 499,6 (nível deficiente), 499,6 a 697,7 (nível baixo) e > 697,7 (nível aceitável) 9 .…”
Section: Métodosunclassified
“…Considering this aspect, nutritional biomarkers, such as circulating carotenoids, folate and vitamin E, represent an additional measure to guarantee the quality of dietetic information since they do not depend on memory and are not prone to the same type of measurement errors (20,21) . Plasma concentrations of carotenoids and folate are associated with recent F&V intake (22)(23)(24) , and vitamin E status has been considered a good indicator of healthy food choices (25) .…”
mentioning
confidence: 99%